2018
DOI: 10.7322/jhgd.152187
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective study of the epidemiological overview of the transmission of Chagas disease in the State of Acre, South-Western Amazonia, from 2009 to 2016

Abstract: Introduction: Chagas disease (CD), also known as American Trypanosomiasis, is an infectious parasitic disease caused by the etiologic agent Trypanosoma cruzi. It is considered endemic in the low-income population and is classified by the WHO as a neglected tropical disease. In the state of Acre, there is almost no scientific data regarding the epidemiology of CD, even though the first autochthonous case was registered in the 1980s. Objective: To analyze the epidemiological panorama of the transmission of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 39 publications
1
13
0
2
Order By: Relevance
“…Results of other studies conducted in the same geographical region corroborate with those of our study, which reported a higher rate of infection in rural areas. This finding is because of the populations' higher consumption of açaí and the processing of this fruit without following proper sanitary procedures, thus increasing the possibility of outbreaks by oral transmission 10,14 .…”
Section: Discussionmentioning
confidence: 99%
“…Results of other studies conducted in the same geographical region corroborate with those of our study, which reported a higher rate of infection in rural areas. This finding is because of the populations' higher consumption of açaí and the processing of this fruit without following proper sanitary procedures, thus increasing the possibility of outbreaks by oral transmission 10,14 .…”
Section: Discussionmentioning
confidence: 99%
“…However, most of the species described in the previous paragraph, have not yet been recorded in Jurua Valley, a region that borders Peru, and has Cruzeiro do Sul as its main city, a region in which Chagas disease outbreaks have already occurred, but only a few studies have been carried out in this area 6 . This is the reason why additional studies are welcome in this region in order to understand the diversity of Chagas disease vectors.…”
Section: Introductionmentioning
confidence: 99%
“…Although the first case of CD in the state of Acre was recorded in the 1980s (Barata et al 1988), it was the outbreaks from 2016 onwards that raised the concern about the disease, given the increase in notifications and its intrinsic relationship with the consumption of contaminated food. An example is the outbreak that occurred in the municipality of Rodrigues Alves in 2016 (Oliveira et al 2018). Since there are no studies on the vector species occurring in this region, studies are needed to increase the knowledge about this subject and thus raise the community's awareness of prophylactic measures, serving as a tool for guiding health surveillance in the establishment of strategies for combating new outbreaks.…”
Section: Introductionmentioning
confidence: 99%
“…Since there are no studies on the vector species occurring in this region, studies are needed to increase the knowledge about this subject and thus raise the community's awareness of prophylactic measures, serving as a tool for guiding health surveillance in the establishment of strategies for combating new outbreaks. Thus, this study is aimed at investigating the occurrence of triatomines and their infection by T. cruzi in an area of CD outbreak in the municipality of Rodrigues Alves, Acre, Brazil, where an outbreak was reported with five cases confirmed during February 2016, all of them apparently caused by oral transmission, probably by consumption of "açaí" juice contaminated with feces from triatomines (Oliveira et al 2018).…”
Section: Introductionmentioning
confidence: 99%